Posterior Reversible Leukoencephalopathy Syndrome in a Patient after Acute COVID-19 Infection - Ketino Kobaidze; Yoo Mee Shin; Mariam Japaridze; Ioannis Karakis; Xin Wu (Case Reports in Neurological Medicine)
A 90-year-old African American female with multiple comorbidities and a severe COVID-19 infection was discharged home in stable condition after two weeks of hospitalization. A week later, she developed new-onset generalized tonic-clonic seizures requiring readmission to the hospital. The patient’s clinical course and brain imaging supported PRES. Her mentation returned to baseline with supportive care and anticonvulsant treatment. Follow-up brain MRI four months later demonstrated resolution of FLAIR signal abnormalities confirming PRES. SARS-CoV-2 insult on the cerebrovascular endothelial cells likely continued and despite the clinical recovery eventually resulted in PRES. We believe that this is the first case describing the presentation of PRES after recovery from severe acute COVID-19 infection.